2017
DOI: 10.1186/s12868-017-0354-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of conservative interventions for sickness and pain behaviors induced by a high repetition high force upper extremity task

Abstract: BackgroundSystemic inflammation is known to induce sickness behaviors, including decreased social interaction and pain. We have reported increased serum inflammatory cytokines in a rat model of repetitive strain injury (rats perform an upper extremity reaching task for prolonged periods). Here, we sought to determine if sickness behaviors are induced in this model and the effectiveness of conservative treatments.MethodsExperimental rats underwent initial training to learn a high force reaching task (10 min/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 74 publications
0
40
1
Order By: Relevance
“…This interpretation is consistent with those of Xin et al . , who reported that inflammation and pain in a WMSD model (albeit using a different force magnitude from that in our study, i.e., a difference in intensity in task performance) do not involve the same pathway. Elliott et al .…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…This interpretation is consistent with those of Xin et al . , who reported that inflammation and pain in a WMSD model (albeit using a different force magnitude from that in our study, i.e., a difference in intensity in task performance) do not involve the same pathway. Elliott et al .…”
Section: Discussioncontrasting
confidence: 65%
“…In addition, upregulation of NGF and GDNF in EDL muscle was essential to mechanical hyperalgesia in an animal model of DOMS, caused by repeated lengthening contractions . DOMS after intense acute swimming, leading to upregulated TNF‐α in soleus muscle, was required for mechanical hyperalgesia . Accordingly, we measured NGF, GDNF, and TNF‐α levels in FDS muscle to investigate the mechanism of muscle mechanical hyperalgesia caused by continuing repetitive reaching and grasping tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An early treatment timepoint was chosen to tease out whether CCN2 plays a key role in the progression of fibrosis in this chronic overuse model, or if persistent mechanical loading alone increases collagen production through TGFβ1 signaling pathways independent of CCN2 . As indicated above, increased muscle levels of CCN2 and TGFβ1 are already present in 0‐week HRHF rats, yet, indices of central sensitization (i.e., spinal cord changes associated with chronic pain) are not detectable until HRHF week 6 . This earlier timepoint allowed us to avoid central nervous system changes that would confound interpretation of behavioral findings.…”
Section: Discussionmentioning
confidence: 99%
“…Custom‐designed operant behavioral chambers were used in which rats performed an operant reaching and lever pulling task, as previously described 32‐34 . As an overview, task rats were shaped for 6 weeks to learn a reaching and lever‐pulling task at high force loads.…”
Section: Methodsmentioning
confidence: 99%